Theology and dialogue Essays in conversation with George Linkbeck - Marshall, Bruce (Notre Dame University of Notre Dame Press, 1990)
A collection of essays proposing constructive directions for the future of Christian theology. The contributors deal with the question of how the present task of theology should be conceived, and also examine historical and contemporary cases of the dialo
Keywords: Lindbeck, George A. Theology. Lindbeck, George A. -- 1923-2018 Bibliografie Theologie Dialoog. Lindbeck, George A Theology